Investigation of relative intensity noise in asymmetric external cavity semiconductor laser sensors: Influence of dual-line spectral separation and linewidth enhancement factor - Shrestha, Jyoti C.; Blom, Sven; Witzigmann, Bernd; Hillmer, Hartmut H. (IEEE Sensors Journal, 2015)
A tunable gas sensor based on an asymmetric external cavity semiconductor lasers oscillating on two spectral lines is presented and investigated experimentally and theoretically. In order to minimize the cost and size of the gas sensor, relative intensity noise (RIN) as a detection methodology is used to measure the intensity levels and intensity differences of two lines. The influence of the spectral separation of the two lines on the RIN has been investigated and explained in the framework of the interplay of the linewidth enhancement factor and two different cavity lengths of the two lines. Each line is related to a different cavity length, which we denote as an asymmetric laser. It has been found that for larger line spacing, the sensor reveals a higher sensitivity to intensity variations of the lines than for smaller line spacing. The experiments show the largest change of RIN at an intensity difference between the two lines of -5 and +5 dB. Very interesting is the experimental result that each line can be tuned in a stable single line condition. For a line intensity ratio between -40 and -15 dB as well as around +20 dB, two ranges of constant RIN have been found, which are different in the averaged RIN by ≈ 6 up to 10 dB depending on the line separation. The difference of ≈6 up to 10 dB can be quantitatively explained by the asymmetric cavity design and linewidth enhancement factor.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Asymmetric laser cavity; line spacing; relative intensity noise (RIN); semiconductor lasers; sensors